Evaluating the Effectiveness of Gamification on Employee Engagement and Consistency in a Weight Loss Challenge Program at PT Kereta Api Indonesia (Persero) DAOP 1 Jakarta - Maya Sari, Raden Rahayu; Rinawan, Fedri Ruluwedrata (Devotion : Journal of Research and Community Service, 2026)
PT Kereta Api Indonesia (Persero) views its employees as strategic assets, whose well-being directly affects organizational performance. Rising rates of overweight and obesity pose health and productivity challenges, increasing risks of fatigue and chronic disease. This study aims to evaluate the effectiveness of gamification in improving employee engagement and consistency during the Weight Loss Challenge program at PT Kereta Api Indonesia (Persero) DAOP 1 Jakarta. A total of 98 employees with a Body Mass Index (BMI) of ≥30 kg/m² participated in the program over a three-month period. Health indicators were measured using BMI and the percentage of weight loss, while engagement was evaluated through a point system, sharing activities, and webinar participation. Analysis using paired-sample t-tests and cross-tabulation with chi-square tests revealed a significant decrease in average BMI by 1.79 kg/m² and an average weight loss percentage of 6.16%, both statistically significant (p < 0.001). Outcome-oriented and behavior-intensive components, such as weight loss and activity points, showed a very strong relationship with the participants' final scores, while supportive components like sharing activities and webinar participation showed moderate influence. The findings suggest that gamification effectively promotes healthy behavior changes through increased employee engagement and consistency. Programs with measurable, intensive activities boost participation and support sustainable workplace health and productivity.